Mediation in the criminal procedure code of Malaysia - Ab Aziz, Norjihan (IIUM Press, International Islamic University Malaysia, 2017)
Settlement out of court in criminal cases in Malaysia is allowed through the process of plea bargaining which is accepted officially after the amendment of the Criminal Procedure Code 2012 (Act 539) by the Criminal Procedure Code (Amendment) Act 2012. In the process of plea bargaining, the prosecution and the accused negotiate on the reduction of charge or sentence against the accused. In the case that attempts at plea bargaining fail, the Court at the case management stage will fix a date for trial. Nevertheless, the United Kingdom, Singapore and the State of Idaho have taken a proactive step which allows a judge to act as a mediator to facilitate the process of plea bargaining between the prosecutor and the accused to reach an agreement out of court known as criminal mediation.